Estudo da impermeabilização, monitoramento, modelagem e simulação de cenários para a bacia do Barbado - Cuiabá/MT - Faria, Nilma de Oliveira (Universidade Federal de São Carlos, 2012)
This paper aims to hydrologically simulate the Barbado Stream watershed, located in Cuiabá-MT, by using the SWMM model and evaluate the responses to its different waterproofing scenarios. The acquisition of the input data for the simulation involved monitoring rainfall and flow rate; geoprocessing techniques to estimate physical characteristics of the watershed and assist the study of its sealing, which in turn, conducted the on-site survey of permeable areas (AP) directly connected impervious areas (AIDC) and unconnected impervious areas (AInc) for a sample of lots included in the study watershed. Hydrological monitoring was carried out for the Barbado Stream s local precipitation, water level and velocity during precipitation events, which allowed the construction of a rating curve for the monitoring section up to the stage of 80 cm, extrapolated up to the stage of 2,60 m. The results of the sealing study revealed that the waterproofing mean of occupied lots in the watershed studied is of 82.40% and the percentage of waterproofing in the total area of the studied watershed is 55.07%. During calibration, a sensitivity analysis of the parameters was held, resulting as the most sensitive parameters the sealed area (AIDC) and the Manning s roughness coefficient for channels. The calibration, performed by trial and error for two events, presented a satisfactory adjustment shown by the average determination coefficient of 0.912, Nash-Sutcliff coefficient of 0.842 and 0.025% of average error between the peak flows observed and estimated by the model. The model validation was verified for two events with adjustments close to those found in calibration. The simulation of rainfall scenarios for rainfall return periods of 2 up to 100 years revealed an increase in the peak flow of 12.6% to 16.9% for Scenario 2 and an increase from 11.7% to 22.0% for Scenario 3, both compared to the current occupation of Scenario 1. Even for return periods of 2 years, floods were found in scenario 1 at one point and in scenarios 2 and 3 in three points.
Keywords: Drenagem urbana; Calibração; SWMM (Programa de computador); Cenários; Impermeabilização; Urban Drainage; Calibration; SWMM; Scenarios; Waterproofing; ENGENHARIAS::ENGENHARIA CIVIL